Humanitarian intervention: Before and after responsibility to protect (R2P) assessing the impact of R2P - Abdelhady, Amr (AUC Knowledge Fountain, 2016)
The main topic of this thesis is to tackle the principle of Humanitarian intervention. Responsibility to Protect (R2P) was coined in 2001 as an evolution to the doctrine of Humanitarian Intervention (HI) with the aim to set precautions and conditions to govern the way the international community responds to humanitarian crises. The absence of defined rules or regulations to govern the international community’s response to humanitarian crises has rendered the doctrine of humanitarian intervention perceived as a tool that can be used selectively by major powers to intervene in other countries according to their interests. The case of Kosovo (1999) when NATO forces launched military attacks against the Former Yugoslavian Republic (FYR) without a mandate from the UN Security Council, made it clear that the time was ripe by then for the adoption of a principled framework for humanitarian intervention. This framework was then proposed and coined later by the International Commission on Intervention and State Sovereignty (ICISS) and named the Responsibility to Protect (R2P). However, after the launch of R2P (2001) and the adoption of R2P at the UN World Summit (2005), the developments in Libya (2011) and Syria (2011-?) revealed that R2P has not provided substantive change to the pattern of the state reactions to humanitarian crises, political interests remained the dominant factors deciding intervention in case of humanitarian crises before and after R2P The thesis views that the launch of R2P constituted a historical opportunity to promote parameters and conditions for the international community to respond to humanitarian crisis in an automatic way away from any other considerations that could stem from particular interests or rivalry among major powers. However, the pattern of the international intervention in humanitarian crises after the R2P remained problematic. The main hypothesis of the thesis is throughout ages political interests were the dominant motive behind the decision of international intervention in humanitarian crises. Despite the great aspirations that accompanied the adoption of R2P, the pattern of international intervention under humanitarian reasons remained under the effect of the dominance of the political interests as it used to be before the adoption of R2P. The thesis will study different patterns of intervention in different eras before and after the adoption of R2P in order to demonstrate that political interests remained the dominant motive behind the decision of international intervention in humanitarian crises before and after R2P.